2022
DOI: 10.3390/su14169813
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Energy Efficiency Measures’ Impact on Energy Performance in the Educational Building of Kazakh-German University in Almaty

Abstract: As climate change concerns are rising rapidly, energy efficiency promotion and implementation could be sustainable solutions within energy transition. In this context, buildings, including educational ones, play an important role in reducing energy needs and promoting energy efficiency since they account for a significant share of the total energy consumption. As a case study for this research, the educational building of Kazakh-German University was selected. Following the national and international building … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…The assessment of retrofitting measures on the energy efficiency performance of the buildings was conducted, and the resulting impact was calculated for an educational building of Kazakh-German University. Their results indicated that minor retrofitting interventions provide energy savings of up to 36.9 kWh/m 2, and in the major scenario, the savings were 77.76 kWh/m 2, reducing up to 82% CO 2 emission [49].…”
Section: Interventionsmentioning
confidence: 99%
“…The assessment of retrofitting measures on the energy efficiency performance of the buildings was conducted, and the resulting impact was calculated for an educational building of Kazakh-German University. Their results indicated that minor retrofitting interventions provide energy savings of up to 36.9 kWh/m 2, and in the major scenario, the savings were 77.76 kWh/m 2, reducing up to 82% CO 2 emission [49].…”
Section: Interventionsmentioning
confidence: 99%
“…In [20], the authors studied the energy saving potential of an existing Kazakh-German educational building. The authors explain that choosing optimal retrofit alternatives in non-domestic buildings is a difficult task.…”
Section: Introductionmentioning
confidence: 99%
“…In a case study of the Kazakh-German University in Almaty, Kazakhstan, retrofitting measures were found to reduce CO 2 emissions by 48-82%. [20]. In general, educational buildings have great potential as locations where GHG emissions can be reduced through energy efficiency measures and RE utilization.…”
Section: Introductionmentioning
confidence: 99%